1999
DOI: 10.1103/physrevlett.82.81
|View full text |Cite
|
Sign up to set email alerts
|

Induced Coherence and Stable Soliton Spiraling

Abstract: We develop a theory of soliton spiraling in a bulk nonlinear medium and reveal a new physical mechanism: periodic power exchange via induced coherence, which can lead to stable spiraling and the formation of dynamical two-soliton states. Our theory not only explains earlier observations, but provides a number of predictions which are also verified experimentally. Finally, we show theoretically and experimentally that soliton spiraling can be controled by the degree of mutual initial coherence.Self-guided optic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…(27) only depends on the parameter s, not on p. We have checked numerically that this integral never vanishes for any s. Thus, the condition (27) is satisfied only when p = ±1. In this case, it follows from (13), (19) and (24) that w 1 = φ(r)e ±iθ , u 2 = u 20 (r), and w 3 = f (r)e ±iθ . We can continue the perturbation series expansions (14)- (16) to higher orders and find that all u 2n (n ≥ 0) corrections are only functions of r, and all w 2n+1 (n ≥ 0) corrections have the form g(r)e ±iθ .…”
Section: A Vortex Solitonsmentioning
confidence: 98%
“…(27) only depends on the parameter s, not on p. We have checked numerically that this integral never vanishes for any s. Thus, the condition (27) is satisfied only when p = ±1. In this case, it follows from (13), (19) and (24) that w 1 = φ(r)e ±iθ , u 2 = u 20 (r), and w 3 = f (r)e ±iθ . We can continue the perturbation series expansions (14)- (16) to higher orders and find that all u 2n (n ≥ 0) corrections are only functions of r, and all w 2n+1 (n ≥ 0) corrections have the form g(r)e ±iθ .…”
Section: A Vortex Solitonsmentioning
confidence: 98%
“…Theoretically, vector-soliton collisions have been studied intensively in the past ten years. It has been shown that soliton transmission, reflection, trapping and spiraling can all occur [6,7]. More surprisingly, a fractal structure has been found where transmission, reflection and trapping occur in an intertwined, fractal manner [8].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include pulse propagation in birefringent fibers and wavelength-divisionmultiplexed systems [1,2], operation of optical logic gates [3], and beam steering in Kerr or photo-refractive crystals [4][5][6]. Theoretically, vector-soliton collisions have been studied intensively in the past ten years.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the dipole excitation is so strong that the structure behaves as a pair of spiraling beams earlier analyzed in Ref. [8]. This is only one of many interesting phenomena observed in simulations which also include excitation of rotational modes by collision with a scalar soliton, annihilation or strong deflection of the incident soliton, etc.…”
mentioning
confidence: 99%
“…We consider the propagation of two coherent light beams interacting incoherently in a saturable nonlinear medium. In the paraxial approximation, the beam mutual interaction can be described by a system of two coupled nonlinear Schrödinger (NLS) equations [3][4][5]8],…”
mentioning
confidence: 99%